Psychological factors as predictors of job performance among teachers in Iseyin local government, Oyo state (2013)
The study investigated the predictive value of emotional intelligence, psychological well-being, teacher efficacy and locus of control as correlates of job performance among teachers in Iseyin Local Government, Oyo State. The study adopted a survey research design. The participants in the study were 300 (male -135, female =165) teacher from government owned schools in Iseyin Local Government, Oyo State. Their age ranged between 24 years and 56 years with mean age of 34.6 years. Five valid and reliable instruments were used to assess emotional intelligence (a=.78), psychological well-being (α=.84), teacher efficacy (α=.64), locus of control (a=.72) and job performance (α=.64). Descriptive statistics, Pearson's Product Moment Correlation and multiple regression analysis were used to analyse the data. The results revealed that emotional intelligence, psychological well-being, teacher efficacy and locus of control were potent predictors mildly associated to job performance. The study has implications for government, that teachers should understand their emotions and express themselves in order to relate well with others so as to successfully cope with the demands of daily life and there is need for Government and management of organizations to consider some formative factors identified to be the strong influence of job performance and integrate them in any employees' development programmed to improve employees' performance in the workplace. Therefore, it will be a great importance for managements, government agencies, grass-root governments and establishments to understand and design policies or strategies to improve on their workers' performance.